Advances of climate modelling for policy analysis - Francesco Bosello; Carlo Carraro; Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper surveys recent advances in climate models by emphasising how quantitative instruments can answer the main crucial questions addressed by the policymakers involved and therefore aid the formulation of effective global climate policies. The limits of existing models are highlighted and new ideas and developments are shown to increase the reliability of climate models for policy analysis. It is also suggested that the complexity and uncertainties surrounding climate issues are difficult to translate into adequate policies without the help of sophisticated and integrated global quantitative modelling.
Keywords: C5; C6; D6; D9; O13; 330; Environmental modelling; Climate change; Policy analysis; Integrated assessment; Umweltpolitik; Klimaschutz; Wirtschaftsmodell; Theorie